BHK cell suspension cultures and foot and mouth disease virus production for vaccines - ΠΑΠΠΟΥΣ, Χ.; ΒΕΡΜΠΕΛΗΣ, Π.; ΔΗΜΗΤΡΙΑΔΗΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
Using the BHK cell suspension culture method in fermentor of 100 It capacity 1,5 — 3 χ IO6 cells/ml are obtained in 48 — 72 hours. The cells maintain their susceptibility to the vaccine strains of F.M.D. virus and the parameters of the virus produced on such cells are satisfactory. Vaccines prepared with this virus induced good immunity for bovines and sheep.